Youth Dance: The Guidelines for Music Teaching Methods at Nanning Normal University - Jie, Xu; Hiranrak, Sakchai (Journal of Roi Kaensarn Academi, 2024)
Dalcroze's music teaching method and Comprehensive Musicianship teaching method are world-famous music teaching methods. This article aims to study Dalcroze and Comprehensive Musicianship teaching methods to guide students majoring at Nanning Normal University. As it is phase 1 of the research, the researcher chose to use qualitative research by reviewing documents and receiving suggestions from experts. To gain knowledge about music teaching methods for music major students at Nanning Normal University. Conducted between June and September 2023. The research results found that 1) The study compares Dalcroze's Eurhythmics and Comprehensive Musicianship instructional methodologies for middle school music classes. Eurhythmics is an interactive approach that combines music, improvisation, and discovery-based learning. Comprehensive Musicianship, an interdisciplinary approach, emphasizes skill development, historical background, singing correct pitches, sight-reading, and interpretive elements. 2) The "Youth Dance" lesson plan integrates Dalcroze's physical rhythm and Comprehensive Musicianship for middle school music classes. The lesson aims to enhance students' understanding of Uyghur music, develop singing abilities, grasp song moods, and appreciate youth. The lesson includes listening, visual, kinesthetic, and student-centered approaches. 3) The "Youth Dance" is a traditional Uyghur folk song from Xinjiang, China, expressing the essence of youth. The teacher plays the dance video, introduces percussion instruments, and encourages students to contribute lyrics and sing the song. The goal is to promote the development of Chinese national music and cherish the beauty of youth.